STRATEGI PENGEMBANGAN USAHA TAHU RUMAH TANGGA - Gustina Siregar; Salman ,; Lena Wati (AGRIUM: Jurnal Ilmu Pertanian, 2014)
Tahu is a well known home industry in subulussalam. Municipality competition in the business requires a good strategy to survive in the industry. The aims of the research are to: 1) identify the influence of  internal and external environments to words tofu industry development, 2) give recomended development strategy for tofu makers at simpang kiri subulussalam.Method used in this research is qualitative analysis, the research was condicted at Simpang Kiri, Subulussalam. Data collection technique was done through interviuw and the data were analyzed using SWOT analysis method, sampling technique used random sampling method. Data collection consist of primary and secondary data.Results of descriptive metodology using SWOT  analisis show that matrix value of internal factor is 2,288 while matrix value of external factor is 2,162. The application strategy is done agressively explained as tofu industry is a promising business or has strenght and oppotunity. Recomenended strategy is taking advantage of oppotunities to get profits.Keywords: development strategy, SWOT, IFAS, EFAS